Ebony dreams. A look at jurisprudence and life in the 18th-19th centuries - Cieza Mora, Jairo (2011)
I thought about doing this work once upon a time when appreciating with academic curiosity, some time ago, the excellent catalogs on the Royal Treasury (1567-1820) and Truxillo Corregimiento (Volumes 1 and 11) (1537-1784) published by the Regional Archive of La Libertad, an institution where the documentary heritage of the La Libertad Region is protected, a geographical space where many of the cases that will be commented on take place. Reading the aforementioned catalogs and having in view the palographed documents thanks to the generosity of the Director (already for more than thirty years) of the Regional Archive of La Libertad and the author of the paleographies and transcriptions, Dr. Walther Arteaga Liñán, unfortunately not physically present among us, I decided to do this legal-historical article about slavery on the Peruvian coast from the perspective of a lawyer who knows that isolated law is nothing since it is essentially an interdisciplinary science. In this case, history will allow us to analyze through the old files the life and suffering of people who suffered a disgraceful life and who found a small fissure in the Royal Court, in the Ecclesiastical Court or in the competent regional authorities, which the The slave system allowed them to achieve a life more in line with their status as people using writing, through third parties, and thus achieve an improvement as we will see in the analysis of some cases.